Tracing Motivation in Modern Workplaces: A Two-Decade Bibliometric Insight and Research Mapping - Lusiana, Herlina; Firdaus; Mursanto; Lamsah; Teguh Wicaksono (International Journal of Economics, Business and Innovation Research, 2025)
Motivation in modern workplaces has evolved significantly over the past two decades, shaped by technological disruption, changing work paradigms, and shifting employee expectations. This study aims to systematically trace the conceptual, thematic, and collaborative development of workplace motivation research through a comprehensive bibliometric analysis. Drawing on 300 peer-reviewed journal articles published between 2001 and 2021, data were sourced from Scopus and Google Scholar using the search phrase “understanding motivation in modern workplaces.” The analysis employed VOSviewer software to generate network, overlay, density, and co-authorship visualizations, while data selection followed the PRISMA framework to ensure relevance and transparency. Findings reveal a major shift from traditional constructs such as performance and job satisfaction to emerging themes including psychological well-being, digital leadership, remote work, and meaningful work. The evolution indicates a transition from incentive-based to experience-centered motivation theories, reflecting broader sociotechnical changes. However, the study also uncovers thematic blind spots—such as sustainability-related motivation and employee values—and highlights the fragmented nature of global research collaboration. These insights underscore the need for integrative, cross-disciplinary, and future-oriented frameworks in understanding motivation. This study contributes to the literature by offering a aiming to enhance engagement and well-being in increasingly digital and hybrid work environments.